Euphorbia Section Hainanensis (Euphorbiaceae), a New Section Endemic to the Hainan Island of China From Biogeographical, Karyological, and Phenotypical Evidence - Tian, Xinmin; Wang, Qiuyan; Zhou, Yongfeng (Frontiers in Plant Science, 2018)
Euphorbia hainanensis is an endangered species endemic to the tropical Hainan Island in southern China and of historical importance for Chinese medicine. It is currently the only unplaced species of the genus Euphorbia (Euphorbiaceae) due to its isolated island distribution and debated placement by previous molecular phylogenetic study. We sequenced nuclear ITS and chloroplast rbcL and ndhF for newly collected accessions of E. hainanensis and additional Euphorbia species found in Hainan, and analyzed the sequences in the context of the entire genus together with published data. All gene regions highly supported that E. hainanensis occupied an isolated phylogenetic position, showing no close affinity with any known Euphorbia sections suggesting it was a new section. ITS placed E. hainanensis sister to sect. Crossadenia (subgenus Chamaesyce) from Brazil with an estimated divergence time of 9.3-30.6 Mya while the chloroplast markers placed E. hainanensis at a position sister to the entire New World clade of Euphorbia subgenus Chamaesyce. In addition, our karyological results suggested a close affinity between E. hainanensis and the New World species of Euphorbia subg. Chamaesyce, with which shared the same chromosome number 2n = 28 and basic chromosome number X = 7. Phenotypically, E. hainanensis is unique with no close resemblance to other species in Euphorbia subg. Chamaesyce. Based on its isolated biogeographical, karyological, and phenotypical position, we propose a new section E. subgenus Chamaesyce section Hainanensis that might origin from long distance dispersal events because collective evidences showed a close affinity between this species with those from the New World instead of those from the Old World.